Iatrogenic Arterial Spasm Relieved by Intraarterial Mannitol Infusion - Fortin, David; Osztie, Eva; Neuwelt, Edward A. (American Journal of Neuroradiology, 2000)
Summary: Catheter placement for blood brain–barrier disruption and enhanced chemotherapy delivery can sometimes trigger arterial spasm of moderate-to-severe degree. A slow infusion of a small quantity of intraarterially administered mannitol (10 mL of 25% mannitol) was evaluated as a means to obtain a rapid resolution of catheter placement–induced spasm. We prospectively report 12 consecutive cases of blood brain–barrier disruption among patients who developed catheter placement–induced spasm that was treated by this means without side effects, resulting in rapid resolution of spasm.